Three cases of appendicitis with anorexia nervosa under inpatient care. Issue 1 (December 2015) - Takakura, Shu; Yokoyama, Hiroaki; Suzuyama, Chie; Tatsushima, Keita; Yamashita, Makoto; Gondou, Motoharu; Morita, Chihiro; Hata, Tomokazu; Takii, Masato; Kawai, Keisuke; Sudo, Nobuyuki
Abstract Background Little is known about the occurrence of appendicitis during the re-nourishment period in anorexia nervosa (AN). We report three cases of appendicitis in patients with AN that occurred after hospitalization for treatment of AN. Case presentation Case 1 is a 34-year-old female, case 2 is a 17-year-old female and case 3 is a 38-year-old female. Constipation was observed in all three cases. Careful management of defecation might be essential to prevent appendicitis among AN patients during the re-nourishment period under inpatient care. In addition, mild and diffuse symptoms were observed in all three cases. Therefore, diagnosis proved to be difficult to make and abdominal computed tomography was particularly helpful in all cases. As the symptoms were diffuse, the condition of appendicitis turned out to be more severe and complicated in one case. Additionally, the incidence of appendicitis in AN in the current study might be higher than that in the normal population. Conclusions These findings suggest that appendicitis should be considered as one of the potentially important complications in the therapy for AN.